Coal, Cumulative Impacts, and the Great Barrier Reef. Issue 3 (18th November 2015) - Grech, A.; Pressey, R.L.; Day, J.C.
Abstract: The Great Barrier Reef World Heritage Area, Australia, covers over 348, 000 km 2 of tropical marine ecosystems of global significance. In July 2015, the World Heritage Committee called attention to the cumulative impacts of climate change, poor water quality, and coastal development on the region's outstanding universal value, but stopped short of inscribing the Great Barrier Reef on the List of World Heritage in Danger. Restoring the region's values is hindered by an environmental decision‐making process that fails to incorporate cumulative impacts, including the climate change impacts of greenhouse gas emissions sourced from one of Australia's largest exports, thermal coal. We identify policy and processes that enable a more comprehensive consideration of the cumulative effects of coal mining by environmental decision‐makers. Implementing cumulative impact assessment requires a collaborative and transparent program of planning and monitoring independent of Government and mine proponents that evaluates local, regional, and global impacts. The future of the Great Barrier Reef depends on transformational change in the cumulative assessment of Australian coal mines.